SIKAP GURU TENTANG PEMBELAJARAN TEMATIK DAN PENILAIAN AUTENTIK PADA SEKOLAH DASAR RINTISAN PENERAPAN KURIKULUM 2013 DI KABUPATEN SIGI - Ardin, Ardin (JSTT, 2015)
This research aimed to describe teachers’ response on thematic learning and authentic assesment at piloting elementary schools of Kurikulum 2013 in Sigi. The research implemented qualitative-descriptive method. The sample of the research was 31 teachers from the piloting schools (as saturation sample. Instrument of the research were questionnaire and observation sheet. Research data were analized using descriptive method. Based on analysis, it could be concluded that the teachers’ response was positive category. The teachers like to learn the both systems but have not fully implemented them in the learning process. Prepared lesson plans have not been fully applied in the classroom. It is needed assitence for the teachers as part preparation of the curriculum implementation.